Development Of Video As A Counseling Media That Supports The Provision Of A Balanced Nutrition Menu To Toddler Ages 2-5 Years With Lack Of Nutrition - Nana, Dwi Ratna; Shinta Fauziah; Suri Nurharjanti Harun; Nealy Ulfa Khasanah; Eka Rahmawati (Journal for Quality in Women's Health, 2024)
Background: Toddlers are children aged 12 months to 59 months, where this period is a very crucial period for their growth and development, so it is called the golden period.  Objective : To determine the effect of counseling on the provision of a balanced nutrition menu to mothers who have under-five children aged 2-5 years. Methods: This study uses quantitative analytical methods.  Result: There is an effect There is an effect of counseling giving a balanced nutrition menu to mothers who have under-fives aged 2-5 years on changes in nutritional status based on weight/height and changes in mother's level of knowledge obtained p-value (p < 0.005). Conclusion: This study found the effect of counseling on the provision of a balanced nutrition menu on changes in nutritional status and mother's level of knowledge